VISUAL PRESENTATION IMPLEMENTED IN A NETWORK - Ilo, Jan-Benedict C. and Zaide, Ronald A. 4 0 16; 5 (2005)
u
Thesis (Undergraduate)Pamantasan ng Lungsod ng Maynila, 2005.;BACHELOR OF SCIENCE IN INFORMATION TECHNOLOGY.
Keywords: 2 -- 0; 6; 20; 20; 2